Super-hydrophilic coating for wet-wall cyclone sampling of biological aerosol and preparation method of super-hydrophilic coating

By preparing a superhydrophilic coating on the inner wall of the wet-wall cyclone sampling cup, the problem of particle rebound loss caused by cyclone layer instability and liquid level reduction is solved, and the efficient aerosol-hydrosol transfer of bioaerosol particles is achieved.

CN119955354AActive Publication Date: 2025-05-09RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411948764.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-05-09
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

During the wet-wall cyclone sampling process, the instability of the cyclone layer and the reduction in the liquid level lead to particle rebound losses, making it difficult to achieve high-efficiency aerosol-water sol transfer of bioaerosol particles.

Method used

The superhydrophilic coating is prepared on the inner wall of the wet-wall cyclone sampling cup. By fluorinating the SiO2 nanoparticles and cellulose nanofibers, a superhydrophilic coating liquid is formed, and the inner wall of the sampling cup is coated by impregnation and lifting to prevent the cyclone layer from breaking and the liquid level is lowered.

Benefits of technology

It effectively prevents cyclone fracture and liquid level reduction, reduces particle rebound loss, and improves the sampling efficiency and enrichment effect of bioaerosol particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955354A_ABST
    Figure CN119955354A_ABST
Patent Text Reader

Abstract

According to the super-hydrophilic coating for wet-wall cyclone sampling of the biological aerosol and the preparation method of the super-hydrophilic coating, the inner wall of a sampling cup made of a glass or plastic material is subjected to super-hydrophilic modification, so that a cyclone layer is not prone to breakage in the sampling process, and the cyclone layer is not prone to breakage along with reduction of the liquid level of a liquid sample in the sampling process; the part, which is originally and gradually exposed, on the rotational flow layer is covered by a thin liquid film due to the super-hydrophilic characteristic, so that aerosol particles impact the liquid film layer and are effectively captured, and the particles are prevented from impacting the exposed glass or plastic surface, being rebounded and escaping along with airflow. The method can effectively solve the problem of wall loss during low-flow-rate sampling and long-time sampling, so that efficient aerosol-hydrosol transfer of the biological aerosol particles is realized, the sampling efficiency of the wet-wall cyclone biological aerosol sampler can be greatly improved, and the method has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bioaerosol sampling and super-wetting material preparation, and specifically relates to a super-hydrophilic coating for bioaerosol wet-wall cyclone sampling and a preparation method thereof. Background Art

[0002] Harmful bioaerosols pose a continuous threat to global public safety. The development of practical and real-time bioaerosol monitoring / detection methods remains a continuous challenge. Efficient and full coverage sampling of microbial aerosols is the basis and prerequisite for rapid detection. The sampling principles and methods of bioaerosols and non-biological aerosols are basically the same, that is, the sampling methods are designed according to the physical properties of the aerosols, such as size, weight and charge. Commonly used sampling methods include solid impact, liquid impact, filtration, electrostatic precipitation and condensation sampling. Unlike non-biological aerosols, the research on bioaerosols focuses on microorganisms. Generally, the sampling methods of microbial aerosols are evaluated from aspects such as cell viability, culturability and genetic material integrity, and appropriate sampling methods are selected according to the research content and purpose. Liquid-based sampling methods have less biological damage and are more flexible in sample processing and detection methods. Different subsequent analysis methods can be selected for detection as needed, such as modern analysis and detection methods such as microscopy (electron) microscopy, flow cytometry, ATP bioluminescence method, real-time fluorescence quantitative PCR and immunoenzyme-linked adsorption method.

[0003] The wet wall cyclone method is a variation of the cyclone method and liquid impact sampling. Unlike the common liquid impact aerosol sampler, the wet wall cyclone sampling does not require a high-power sampling pump to provide a high sampling negative pressure. It uses a low-power, high-flow fan to generate a high-speed cyclone in the cyclone chamber, and the centrifugal action generated by the cyclone collects the biological samples in the air onto the liquid film formed by the cyclone. This method can greatly increase the sampling flow rate of the sampler with less sampling liquid, and achieve an enrichment ratio that is difficult to achieve with traditional impact samplers. The collected samples are stored in liquid and are suitable for various types of detection and analysis. During the wet wall cyclone sampling process, the incoming cyclonic airflow forms a cyclonic layer on the inner wall of the cyclonic sampler (usually made of glass or plastic) through centrifugal force and surface tension, and then collects the particles in the air into the liquid flow through inertial impact. However, there are still two problems in the sampling process. First, the instability and unevenness of the swirl will cause the swirl layer to break frequently, especially when the sampling flow rate is low, which will cause it to disintegrate into droplets, so that some particles hit the inner wall of the cup body and rebound and are sucked away with the airflow. This situation will be improved when the flow rate is increased; second, regardless of the sampling flow rate, as the sampling time increases (or the air is very dry, etc.), the sampling liquid level gradually decreases, and the inner surface of the upper part of the cup body that cannot be covered by the liquid swirl gradually increases, so that the impact particles rebound and are sucked away with the airflow, which also causes sampling losses. At present, this problem can be solved to a certain extent by rehydrating while sampling, but due to the influence of multiple factors such as sampling speed and environmental humidity, it is difficult to accurately control the rehydration speed according to environmental changes. Therefore, there is an urgent need for a universal solution that can reduce the rebound loss of particles during sampling.

[0004] In summary, based on the need to develop efficient bioaerosol wet-wall cyclone sampling methods, exploring how to reduce the rebound loss of aerosol particles during wet-wall cyclone sampling to achieve efficient aerosol-hydrosol transfer of bioaerosol particles is a problem that needs to be solved. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] The present invention provides a super-hydrophilic coating for wet-wall cyclone sampling of bioaerosols and a preparation method thereof. By super-hydrophilic modification of the inner wall of a sampling cup made of glass or plastic, the cyclone layer is not easily broken during the sampling process. As the liquid level of the liquid sample decreases during the sampling process, the originally exposed part above the cyclone layer is covered by a thin layer of liquid film due to the super-hydrophilic property, so that particles collide with the liquid film layer and rebound and escape are avoided as much as possible, so as to solve the technical problem of wall loss during low flow rate sampling and long sampling time, and realize efficient aerosol-hydrosol transfer of bioaerosol particles.

[0007] (II) Technical solution

[0008] In order to solve the above technical problems, the present invention proposes a method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling, and the super-hydrophilic coating preparation method comprises:

[0009] S1. fluorination modification of SiO2 nanoparticles and cellulose nanofibers respectively;

[0010] S2. The fluorinated SiO2 nanoparticles and cellulose nanofibers are mixed evenly in anhydrous ethanol to obtain a super hydrophilic coating liquid;

[0011] S3. By dipping and pulling, styrene-butadiene-styrene block copolymer primer and super-hydrophilic coating liquid are sequentially coated on the inner wall of the wet-wall cyclone sampling cup to prepare a super-hydrophilic coating on the inner wall of the cup.

[0012] Furthermore, step S1 includes the following steps:

[0013] (1) dissolving FS-50 fluorocarbon surfactant in water ethanol and stirring at room temperature to obtain a uniform FS-50 ethanol solution, and dividing the FS-50 ethanol solution into two parts;

[0014] (2) Take hydrophilic SiO2 nanoparticles and cellulose nanofibers CNFS, add them into 1 part of FS-50 ethanol solution respectively, stir the reaction at room temperature and then centrifuge, collect the centrifugal products and dry them in a vacuum drying oven to obtain FS-50 modified super hydrophilic SiO2 nanoparticles FS-50@SiO2NPs and FS-50 modified cellulose nanofibers FS-50@CNFS respectively.

[0015] Furthermore, step S1 specifically includes the following steps:

[0016] (1) Dissolve 10 g of FS-50 fluorocarbon surfactant in 100 mL of anhydrous ethanol and stir at room temperature for 40 min to obtain a uniform FS-50 ethanol solution, and divide the FS-50 ethanol solution into 2 parts;

[0017] (2) Take 2 g of hydrophilic SiO2 nanoparticles with an average particle size of 100 nm and 1 g of cellulose nanofibers CNFS, respectively, add them into 1 part of FS-50 ethanol solution, stir the reaction at room temperature for 30 min and then centrifuge. The centrifuged products are collected and dried in a vacuum drying oven to obtain FS-50 modified super hydrophilic SiO2 nanoparticles FS-50@SiO2 NPs and FS-50 modified cellulose nanofibers FS-50@CNFS, respectively.

[0018] Furthermore, in step S1, the centrifuged product is dried in a vacuum drying oven at 120° C. for 12 h.

[0019] Further, step S2 includes the following steps:

[0020] (1) Add FS-50@SiO2 NPs to anhydrous ethanol and disperse them by ultrasonic to obtain a uniform FS-50@SiO2 NPs ethanol dispersion;

[0021] (2) taking rosin resin, adding it to anhydrous ethanol, heating it to fully dissolve the rosin resin, and obtaining an ethanol solution of the rosin resin;

[0022] (3) Mix the FS-50@SiO2 NPs ethanol dispersion with the rosin resin ethanol solution, disperse them by ultrasonic, add FS-50@CNFS, stir and mix, and disperse them by ultrasonic; then add bis(3-trimethoxysilylpropyl)amine, stir and react, and prepare a super-hydrophilic coating liquid.

[0023] Furthermore, step S2 specifically includes the following steps:

[0024] (1) Take 2 g of FS-50@SiO2 NPs, add them to 18 mL of anhydrous ethanol, and disperse them by ultrasonic for 30 min to obtain a uniform FS-50@SiO2 NPs ethanol dispersion;

[0025] (2) taking 4.2 g of rosin resin, adding it to 5 mL of anhydrous ethanol, heating it to 90° C. to fully dissolve the rosin resin, thereby obtaining an ethanol solution of the rosin resin;

[0026] (3) The FS-50@SiO2 NPs ethanol dispersion was mixed with the rosin resin ethanol solution, and ultrasonic dispersion was performed for 30 min. 0.2 g FS-50@CNFS was added, and the mixture was stirred for 10 min and ultrasonic dispersion was performed for 30 min. Then 100 μL of bis(3-trimethoxysilylpropyl)amine was added, and the mixture was stirred and reacted at 45 °C for 2 h to prepare a super-hydrophilic coating liquid.

[0027] Further, step S3 includes the following steps:

[0028] (1) SBS primer coating: butyl acetate is added to SBS adhesive glue, and the mixture is stirred and diluted thoroughly, and then allowed to stand to defoam, to obtain an SBS coating primer; a hole is punched at the bottom of the sampling cup and the outer wall is sealed with a plastic wrap layer; the cup is dipped into the SBS coating primer at a speed of 4500 μm / s and remains there for 10 seconds, and then pulled at a speed of 4500 μm / s and remains there for 2 minutes, and after the butyl acetate evaporates, an SBS gel primer layer is obtained on the cup body;

[0029] (2) Super-hydrophilic coating coating: The cup body coated with the SBS gel primer layer was immersed in the super-hydrophilic coating liquid at a speed of 5000 μm / s and kept for 1 min by dipping and pulling, and then pulled up at a speed of 5000 μm / s and kept for 1 min. After circulating the super-hydrophilic coating liquid twice, it was ventilated and dried to obtain a super-hydrophilic coating.

[0030] Furthermore, step S3 specifically includes the following steps:

[0031] (1) SBS primer coating: add 5 mL of butyl acetate to 50 mL of SBS adhesive, fully stir and dilute for 20 min, and then stand for 2 h to defoam to obtain SBS coating primer; punch a hole at the bottom of the sampling cup and seal the outer wall with a plastic wrap layer; immerse the cup in the SBS coating primer at a speed of 4500 μm / s and stay for 10 s, then pull it at a speed of 4500 μm / s and stay for 2 min, and after the butyl acetate evaporates, obtain an SBS gel primer layer on the cup body;

[0032] (2) Super-hydrophilic coating coating: The cup body coated with the SBS gel primer layer was immersed in the super-hydrophilic coating liquid at a speed of 5000 μm / s and kept for 1 min by dipping and pulling, and then pulled up at a speed of 5000 μm / s and kept for 1 min. After circulating the super-hydrophilic coating liquid twice, it was ventilated and dried for 12 hours to obtain a super-hydrophilic coating.

[0033] In addition, the present invention also proposes a super-hydrophilic coating for bioaerosol wet-wall cyclone sampling, and the super-hydrophilic coating is prepared by the above method.

[0034] In addition, the present invention also provides a wet-wall cyclone sampling cup whose inner wall is modified by the super-hydrophilic coating.

[0035] (III) Beneficial effects

[0036] The present invention proposes a super-hydrophilic coating for bioaerosol wet-wall cyclone sampling and a preparation method thereof. By super-hydrophilic modification of the inner wall of a glass or plastic sampling cup, the cyclone layer is not easy to break during the sampling process, and as the liquid sample level decreases during the sampling process, the part that was originally gradually exposed above the cyclone layer is covered by a thin layer of liquid film due to the super-hydrophilic property, so that the aerosol particles hit the liquid film layer and are effectively captured, thereby preventing the particles from hitting the exposed glass or plastic surface and being rebounded and escaping with the airflow. This method can effectively solve the wall loss problem during low flow rate sampling and long-term sampling, thereby realizing efficient aerosol-hydrosol transfer of bioaerosol particles, and can greatly improve the sampling efficiency of wet-wall cyclone bioaerosol samplers, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1It is a schematic diagram of the principle of the preparation method and application test of the super-hydrophilic coating of the present invention;

[0038] Figure 2 FTIR and XPS characterization of the products FS-50@SiO2 NPs, FS-50@CNFS and super-hydrophilic coating obtained in the examples of the present invention;

[0039] In the figure: a is the FTIR spectrum of SiO2 and FS-50@SiO2 NPs; b is the FTIR spectrum of CNFS and FS-50@CNFS; c is the surface FTIR spectrum of SC and SC-SBS; d is the 1600~1350cm in the surface FTIR spectrum of SC and SC-SBS -1 Magnified image; e is the full XPS scan spectrum of the SC-SBS surface; f is the Si 2p spectrum; g is the C1s spectrum; h is the F 1s spectrum; i is the Na 1s spectrum;

[0040] Figure 3 The SEM and AFM characterizations of the product SC-SBS obtained in the embodiment of the present invention;

[0041] In the figure: a is the SEM image of the SC-SBS surface at a scale of 5 μm; b is the SEM image of the SC-SBS surface at a scale of 2 μm; c is the SEM image of the SC-SBS surface at a scale of 1 μm; d is the element mapping of the main elements Si, C, O, F and Na on the SC-SBS surface; e is the AFM image of the SC-SBS surface;

[0042] Figure 4 is the change of contact angle (CA) when SC-SBS contacts water droplet (0-4s);

[0043] Figure 5 The changes of CA when the coating surface was in contact with the water droplet for 5s during the SC-SBS tape peeling test for different times;

[0044] Figure 6 Characterize the adhesion of coatings by cross-hatch method;

[0045] In the figure: a is the GB / T9286-2021 standard cross-cut method grading diagram, from top to bottom are 0, 1, 2, 3, 4; b is the result of the simple SC layer cross-cut test; c is the result of the SC-SBS cross-cut test;

[0046] Figure 7 Fluorescence measurements after sampling aerosols of fluorescent particles of different sizes with and without ultra-clear water coating;

[0047] In the figure: a is the measurement result after sampling of 0.51μm fluorescent particle aerosol; b is the measurement result after sampling of 1.1μm fluorescent particle aerosol; c is the measurement result after sampling of 2.9μm fluorescent particle aerosol;

[0048] Figure 8 The culture counts after sampling Bacillus subtilis spore aerosols with and without ultra-clear water coating;

[0049] In the figure: a shows the improvement of the sampling enrichment effect with super-hydrophilic coating compared with that without coating at different flow rates; b shows the sampling culture counting statistics with and without super-clear water coating; c shows the sampling culture results with and without super-clear water coating;

[0050] Fig. 9 The ATP fluorescence of the sample liquid is measured after sampling air with and without the ultra-clear water coating at a sampling flow rate of 100L / min. DETAILED DESCRIPTION

[0051] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.

[0052] This embodiment proposes a method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling, and the super-hydrophilic coating preparation method specifically includes the following steps:

[0053] S1. Fluorination modification of SiO2 nanoparticles and cellulose nanofibers

[0054] (1) Dissolve 10 g of FS-50 fluorocarbon surfactant in 100 mL of anhydrous ethanol and stir at room temperature for 40 min to obtain a uniform FS-50 ethanol solution, and divide the FS-50 ethanol solution into 2 parts;

[0055] (2) Take 2 g of hydrophilic SiO2 nanoparticles with an average particle size of 100 nm and 1 g of cellulose nanofibers CNFS, respectively, add them into 1 part of FS-50 ethanol solution, stir the reaction at room temperature for 30 min and then centrifuge. The centrifuged products are collected and dried in a vacuum drying oven at 120 °C for 12 h to obtain FS-50 modified super hydrophilic SiO2 nanoparticles FS-50@SiO2 NPs and FS-50 modified cellulose nanofibers FS-50@CNFS, respectively.

[0056] S2. The fluorinated SiO2 nanoparticles and cellulose nanofibers are mixed evenly in anhydrous ethanol to obtain a super hydrophilic coating liquid.

[0057] (1) Take 2 g of FS-50@SiO2 NPs, add them to 18 mL of anhydrous ethanol, and disperse them by ultrasonic for 30 min to obtain a uniform FS-50@SiO2 NPs ethanol dispersion;

[0058] (2) taking 4.2 g of rosin resin, adding it to 5 mL of anhydrous ethanol, heating it to 90° C. to fully dissolve the rosin resin, thereby obtaining an ethanol solution of the rosin resin;

[0059] (3) The FS-50@SiO2 NPs ethanol dispersion was mixed with the rosin resin ethanol solution, and ultrasonic dispersion was performed for 30 min. 0.2 g FS-50@CNFS was added, and the mixture was stirred for 10 min and ultrasonic dispersion was performed for 30 min. Then 100 μL of bis(3-trimethoxysilylpropyl)amine was added, and the mixture was stirred and reacted at 45 °C for 2 h to prepare a super-hydrophilic coating liquid.

[0060] S3. By dipping and pulling, styrene-butadiene-styrene block copolymer (SBS) primer and super-hydrophilic coating liquid are first coated on the inner wall of the wet wall cyclone sampling cup, and a super-hydrophilic coating is prepared on the inner wall of the cup body.

[0061] (1) SBS primer coating: add 5 mL of butyl acetate to 50 mL of SBS adhesive, fully stir and dilute for 20 min, and then stand for 2 h to defoam to obtain SBS coating primer; punch a hole at the bottom of the sampling cup and seal the outer wall with a plastic wrap layer; immerse the cup in the SBS coating primer at a speed of 4500 μm / s and stay for 10 s, then pull it at a speed of 4500 μm / s and stay for 2 min, and after the butyl acetate evaporates, obtain an SBS gel primer layer on the cup body;

[0062] (2) Superhydrophilic coating coating: The cup body coated with the SBS gel primer layer is immersed in the superhydrophilic coating liquid at a speed of 5000 μm / s and kept for 1 min by dipping and pulling. Then, it is pulled up at a speed of 5000 μm / s and kept for 1 min. After two cycles of immersion coating in the superhydrophilic coating liquid, it is ventilated and dried for 12 hours to obtain a superhydrophilic coating (SC-SBS). The outer wall preservative film layer is removed to obtain a sampling cup with an inner wall modified by the superhydrophilic coating. The bottom hole is sealed for standby use.

[0063] Characterization and testing of FS-50@SiO2 nps, FS-50@CNFS and super-hydrophilic coatings:

[0064] The above-obtained products FS-50@SiO2 NPs, FS-50@CNFS and superhydrophilic coating were subjected to FTIR, XPS, SEM and wettability characterization as well as stability and mechanical property tests.

[0065] (1) FTIR characterization

[0066] The chemical composition of the coating surface was studied by FTIR. Figure 2 a and b are at 711 and 1305 cm -1 、709cm -1 and 1322cm -1 The absorption peak at 1637 cm -1 and 1635cm -1 The absorption peak may originate from the carboxyl group (-COO - ) asymmetric stretching vibration. The above results show that SiO2 nanoparticles and cellulose nanofibers have been successfully modified. In addition, the polar component of the functionalized component may be ~COO - ~Na + , which makes the surface have a strong affinity for polar water molecules and thus superhydrophilicity. At the same time, the infrared spectra of the SBS-free superhydrophilic coating (SC) and the SC-SBS surface ( Figure 2 c) and 1600~1350cm -1 Local magnification shows that SC and SC-SBS have a peak at 1070 cm -1 The peak at 1457 cm corresponds to the asymmetric vibration absorption peak of Si-O. -1 and 1386cm -1 The absorption peak at 2825cm is attributed to the bending vibration peak of -CF3 / -CF2-, indicating that the functionalized nanoparticles are dispersed on the surface of the coating, providing hydrophilic polar groups for the coating. -1 and 2871cm -1 The absorption peak at 1694 cm -1 The peak at 966 cm was assigned to the stretching vibration of C=O, which may come from both the rosin resin and the functionalizing agent FS-50. -1 The absorption peak at 1560 cm-1 only appears in the FTIR spectrum of SC-SBS and is considered to be the characteristic peak of SBS adhesive, which may come from the bending vibration of the CH bond in C=CH. -1 、1540cm -1 、1520cm -1 、1507cm -1 and 1488cm -1The absorption peak at may come from the benzene ring skeleton in the SBS adhesive. Therefore, it can be proved that in addition to being the middle layer of the coating and playing the role of bonding the coating and the substrate, some of the incompletely cured SBS adhesive diffuses to the surface of the coating and constitutes the continuous phase of the coating together with the rosin resin.

[0067] (2) XPS characterization

[0068] XPS was used to study the chemical composition of the coating surface. Figure 2 Figure ei shows the XPS image of the SC-SBS surface. Figure 2 Figure (e) shows a full scan of the coating surface, with photoelectron peaks of Na 1s, F 1s, F KL1, C 1s, O 1s and Si 2p, indicating the formation of a composite coating. Among them, C 1s contains photoelectron peaks of -CF2- and -CF3- groups ( Figure 2 g), the existence of the -CF2- / -CF3- photoelectron peak is also shown in F 1s ( Figure 2 h), Na 1s represents Na + ( Figure 1 i) in the figure indicates the presence of polar components. At the same time, there is a photoelectron peak of SiO2 in Si 2p ( Figure 2 f), indicating that the polar components come from the functionalized nanoparticles FS-50@SiO2, which is the source of the superhydrophilicity of the coating. The presence of -CO- and -C=O- in C1s may be attributed to the presence of rosin resin ( Figure 2 g), thus ensuring the strong adhesion performance of SC-SBS.

[0069] (3) SEM characterization

[0070] SEM images show a large number of irregular protrusions and holes at the micrometer level ( Figure 3 a), the enlarged SEM image shows ( Figure 3 In b and c), these protrusions and holes are composed of many nano-scale particles bonded together, and the overall structure is similar to that of a coral reef, with obvious protrusions and depressions. Figure 3 Figure d is the mapping element distribution of the coating. The image shows that Si, C, O, F and Na elements are evenly distributed on the SC-SBS surface. Among them, F and Na elements are speculated to come from the functionalization reagent, which further verifies that the polar component may be ~COO-~Na+, and is introduced into the coating by forming a uniform dispersed phase composed of functionalized FS-50@SiO2NPs and FS-50@CNFS. In addition, the AFM image shows a rugged mountain-like structure with irregular surface features ( Figure 3(e) The arithmetic mean roughness (Ra) value calculated from the AFM data is 297 nm. In general, this roughness fluctuation helps water droplets quickly penetrate into the pores and gaps and spread out quickly on the coating surface.

[0071] (4) Wettability characterization

[0072] For super hydrophilic coatings, the dynamic change of the water contact angle (CA) on the coating surface can most directly reflect its extreme wetting properties. The contact angle change of the SC-SBS surface was measured using a dynamic contact angle meter. The results are shown in Figure 2. Figure 4 As shown, when the water droplet just contacts the coating surface (0s), the CA is 10.27°, at 1s the CA is 6.86°, at 2s the CA is 5.23°, and at 4s the CA is 4.97°, so SC-SBS has excellent superhydrophilicity.

[0073] (5) Stability and mechanical properties test

[0074] The mechanical stability of the coating is the key to wettability and practical application. The mechanical strength of the coating was tested using a tape sticking-stripping machine. Figure 5 The change in CA of the coating surface when it was in contact with a water droplet for 5 seconds under different tape stripping cycles is shown. Even after 40 tape stripping cycles, the coating surface still maintains excellent superhydrophilicity, and the CA remains below 10° (CA = 6.54°). After 40 tape stripping cycles, the CA of the coating will increase (from 4.72° to 6.54°), but the coating effectively maintains adhesion to the substrate during tape stripping without obvious damage. The GB / T9286-2021 standard cross-hatch method ( Figure 6 a) characterizes the detachment resistance of the coating from the substrate, compared with the pure SC ( Figure 6 Compared with (b), the scratch edges and intersections of SC-SBS are clearly visible, only a small amount of coating falls off, and the affected area is less than 5% ( Figure 6 c), so the detachment resistance level of SC-SBS from the substrate reaches level 1 to 0. The above results show that SC-SBS has mechanical durability and excellent adhesion, which enables it to withstand the challenges associated with repeated tape peeling and strong adhesion requirements, and can resist the shear force of water flow during wet wall cyclone sampling.

[0075] In addition, in order to characterize the tolerance of SC-SBS to the impact and shearing effects caused by high-speed rotating water flow during sampling, 1, 10, 20, and 30 samplings were performed at a sampling flow rate of 300L / min and a sampling time of 10min. Then, 5μL of methyl blue aqueous solution was dripped on its inner surface, and the water impact and shear resistance of the coating were verified by observing the morphology of the water droplets. For the sampling cup without the introduction of the superhydrophilic coating, due to the poor wettability of the polycarbonate material itself, the water droplets were hemispherical on its inner surface and only wetted a small part of the inner surface. After the introduction of the SC-SBS superhydrophilic coating, after one sampling cycle, the water droplets spread on the inner surface of the sampler, and the spreading range was the largest. After 10 (100 min), 20 (200 min), and 30 (300 min) sampling cycles, the water droplets spread on the inner surface of the sampler, and the spreading range slightly narrowed with the increase in the number of sampling times. This may be due to the long-term underwater impact and shearing, which slightly reduced the superhydrophilicity provided by the inner surface coating, but the wetting range is much higher than that of the sampling cup without coating. The above results show that the inner surface of the sampling cup with the SC-SBS coating can withstand long-term water flow shear and impact, meet the requirements of long-term sampling, and has practical application value.

[0076] Wet wall cyclone aerosol sampling performance test evaluation:

[0077] (1) Fluorescent particle aerosol sampling

[0078] Fluorescent particle aerosols were stably generated, and the coated and uncoated sampling cups were used for sampling and enrichment at different flow rates. After sampling, the fluorescence of the sampled liquid was measured to determine the sampling effect. Figure 7As shown in Figures ac, for aerosols of fluorescent particles of different particle sizes, the fluorescence intensity of the sample solution introduced with SC-SBS is significantly higher than that without the introduction of the coating. At the characteristic wavelength of the fluorescent particles used, 484nm, for aerosols generated by fluorescent particles of 0.51μm, at sampling flow rates of 100L / min, 200L / min and 300L / min, the fluorescence values ​​after the introduction of SC-SBS were 6.02, 3.91 and 1.65 times that of the aerosol without the introduction of SC-SBS; for fluorescent particles of 1.1μm, they were 6.66, 3.37 and 1.60 times; for fluorescent particles of 2.9μm, they were 17.24, 5.47 and 6.25 times. This may be because the larger sampling flow rate provides a stronger centrifugal force, so that the liquid film in the cyclone belt can cover a larger area, reducing the area of ​​the gas-liquid cyclone layer and the cyclone layer. The liquid film formed on the inner surface of the sampler with the SC-SBS coating can basically cover the entire sampler even at a smaller flow rate, thereby significantly improving the enrichment effect at a small flow rate, and also having a good improvement effect at a large flow rate. The above results show that the introduction of the SC-SBS coating can significantly improve the enrichment effect of the wet wall cyclone sampler on fluorescent particle aerosols, and the improvement effect is most obvious at a small flow rate.

[0079] (2) Artificial bioaerosol sampling

[0080] Sampling was performed after the Bacillus subtilis spore aerosol was stably generated, and the number of colonies was cultured and counted after sampling to determine the sampling effect. Figure 8 As shown in the figure, when sampling at different sampling flow rates, the sampling enrichment effect of the SC-SBS coating is greatly improved compared with that without coating. In the low flow sampling environment of 100L / min, the enrichment improvement rate is 143.3%, and even in the high flow sampling environment of 300L / min, the improvement rate is 78.5%. And as the sampling flow rate increases, the enrichment improvement rate also tends to decrease overall.

[0081] The above results show that the introduction of SC-SBS coating can significantly improve the sampling and enrichment ability of the wetted wall cyclone sampler for bioaerosol particles, and the improvement effect is most obvious at a smaller flow rate.

[0082] (3) Air sampling

[0083] In order to further verify the actual enrichment effect of the sampler introduced into the SC-SBS on the bioaerosol particles in the atmosphere, the air in the laboratory was sampled simultaneously under the condition of a small flow rate (100L / min), and the ATP fluorescence was used to qualitatively illustrate the sampling effect. Fig. 9As shown, when sampling was performed simultaneously for 5 minutes, 10 minutes, 15 minutes, and 20 minutes, the ATP fluorescence value of the sample liquid after the introduction of SC-SBS sampling was significantly higher than that of the sample liquid without the coating sampling cup, indicating that the former sampled more air microorganisms in the sample liquid.

[0084] The above results show that the introduction of SC-SBS coating can significantly improve the enrichment effect of wetted wall cyclone sampler on bioaerosol particles in the air.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a super-hydrophilic coating for bioaerosol wet-wall cyclone sampling, characterized in that: The super hydrophilic coating preparation method comprises: S1. fluorination modification of SiO2 nanoparticles and cellulose nanofibers respectively; S2. The fluorinated SiO2 nanoparticles and cellulose nanofibers are mixed evenly in anhydrous ethanol to obtain a super hydrophilic coating liquid; S3. By dipping and pulling, styrene-butadiene-styrene block copolymer primer and super-hydrophilic coating liquid are sequentially coated on the inner wall of the wet-wall cyclone sampling cup to prepare a super-hydrophilic coating on the inner wall of the cup.

2. The method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling according to claim 1, characterized in that: Step S1 includes the following steps: (1) dissolving FS-50 fluorocarbon surfactant in water ethanol and stirring at room temperature to obtain a uniform FS-50 ethanol solution, and dividing the FS-50 ethanol solution into two parts; (2) Take hydrophilic SiO2 nanoparticles and cellulose nanofibers CNFS, add them into 1 part of FS-50 ethanol solution respectively, stir the reaction at room temperature and then centrifuge, collect the centrifugal products and dry them in a vacuum drying oven to obtain FS-50 modified super hydrophilic SiO2 nanoparticles FS-50@SiO2NPs and FS-50 modified cellulose nanofibers FS-50@CNFS respectively.

3. The method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling according to claim 2, characterized in that: Step S1 specifically includes the following steps: (1) Dissolve 10 g of FS-50 fluorocarbon surfactant in 100 mL of anhydrous ethanol and stir at room temperature for 40 min to obtain a uniform FS-50 ethanol solution, and divide the FS-50 ethanol solution into 2 parts; (2) Take 2 g of hydrophilic SiO2 nanoparticles with an average particle size of 100 nm and 1 g of cellulose nanofibers CNFS, respectively, add them into 1 part of FS-50 ethanol solution, stir the reaction at room temperature for 30 min and then centrifuge. The centrifuged products are collected and dried in a vacuum drying oven to obtain FS-50 modified super hydrophilic SiO2 nanoparticles FS-50@SiO2 NPs and FS-50 modified cellulose nanofibers FS-50@CNFS, respectively.

4. The method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling according to claim 2 or 3, characterized in that: In step S1, the centrifuged product is dried in a vacuum drying oven at 120° C. for 12 h.

5. The method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling according to claim 1, characterized in that: Step S2 includes the following steps: (1) Add FS-50@SiO2 NPs to anhydrous ethanol and disperse them by ultrasonic to obtain a uniform FS-50@SiO2 NPs ethanol dispersion; (2) taking rosin resin, adding it to anhydrous ethanol, heating it to fully dissolve the rosin resin, and obtaining an ethanol solution of the rosin resin; (3) Mix the FS-50@SiO2 NPs ethanol dispersion with the rosin resin ethanol solution, disperse them by ultrasonic, add FS-50@CNFS, stir and mix, and disperse them by ultrasonic; then add bis(3-trimethoxysilylpropyl)amine, stir and react, and prepare a super-hydrophilic coating liquid.

6. The method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling according to claim 5, characterized in that: Step S2 specifically includes the following steps: (1) Take 2 g of FS-50@SiO2 NPs, add them to 18 mL of anhydrous ethanol, and disperse them by ultrasonic for 30 min to obtain a uniform FS-50@SiO2 NPs ethanol dispersion; (2) taking 4.2 g of rosin resin, adding it to 5 mL of anhydrous ethanol, heating it to 90° C. to fully dissolve the rosin resin, thereby obtaining an ethanol solution of the rosin resin; (3) The FS-50@SiO2 NPs ethanol dispersion was mixed with the rosin resin ethanol solution, and ultrasonic dispersion was performed for 30 min. 0.2 g FS-50@CNFS was added, and the mixture was stirred for 10 min and ultrasonic dispersion was performed for 30 min. Then 100 μL of bis(3-trimethoxysilylpropyl)amine was added, and the mixture was stirred and reacted at 45 °C for 2 h to prepare a super-hydrophilic coating liquid.

7. The method for preparing a super-hydrophilic coating for bioaerosol wet wall cyclone sampling according to claim 1, characterized in that: Step S3 includes the following steps: (1) SBS primer coating: butyl acetate is added to SBS adhesive glue, and the mixture is stirred and diluted thoroughly, and then allowed to stand to defoam, to obtain an SBS coating primer; a hole is punched at the bottom of the sampling cup and the outer wall is sealed with a plastic wrap layer; the cup is dipped into the SBS coating primer at a speed of 4500 μm / s and remains there for 10 seconds, and then pulled at a speed of 4500 μm / s and remains there for 2 minutes, and after the butyl acetate evaporates, an SBS gel primer layer is obtained on the cup body; (2) Super-hydrophilic coating coating: The cup body coated with the SBS gel primer layer was immersed in the super-hydrophilic coating liquid at a speed of 5000 μm / s and kept for 1 min by dipping and pulling, and then pulled up at a speed of 5000 μm / s and kept for 1 min. After circulating the super-hydrophilic coating liquid twice, it was ventilated and dried to obtain a super-hydrophilic coating.

8. The method for preparing a super-hydrophilic coating for bioaerosol wet-wall cyclone sampling according to claim 7, characterized in that: Step S3 specifically includes the following steps: (1) SBS primer coating: add 5 mL of butyl acetate to 50 mL of SBS adhesive, fully stir and dilute for 20 min, and then stand for 2 h to defoam to obtain SBS coating primer; punch a hole at the bottom of the sampling cup and seal the outer wall with a plastic wrap layer; immerse the cup in the SBS coating primer at a speed of 4500 μm / s and stay for 10 s, then pull it at a speed of 4500 μm / s and stay for 2 min, and after the butyl acetate evaporates, obtain an SBS gel primer layer on the cup body; (2) Super-hydrophilic coating coating: The cup body coated with the SBS gel primer layer was immersed in the super-hydrophilic coating liquid at a speed of 5000 μm / s and kept for 1 min by dipping and pulling, and then pulled up at a speed of 5000 μm / s and kept for 1 min. After circulating the super-hydrophilic coating liquid twice, it was ventilated and dried for 12 hours to obtain a super-hydrophilic coating.

9. A super-hydrophilic coating for wet-wall cyclone sampling of bioaerosols, characterized in that: The super hydrophilic coating is prepared by the method according to any one of claims 1 to 8.

10. A wet-wall cyclone sampling cup whose inner wall is modified by the super-hydrophilic coating as claimed in claim 9.

Citation Information

Patent Citations

  • Waterborne super-hydrophilic and super-oleophobic paint and preparation and application methods thereof

    CN109825179A

  • Device and method for collecting and analyzing bioaerosol samples

    CN116916821A

  • Preparation method of hydrophilic-oleophobic coating in air

    CN117511259A

  • Super hydrophilic coating agent and coated film thereof

    JP2018119066A

  • A drone system to search and locate missing persons using mobile signals

    KR102633571B1